Prevalence of severe acute respiratory syndrome coronavirus 2 in the saliva of individuals with coronavirus disease 2019: A cross-sectional study - Nara Santos Araujo; Diana Sofia Patrocinio Paty; Carlos Brites; Denis Damião Costa; Sara Nunes Vaz; Daniele Souza de Santana; Daniel Ribeiro Araki; Jean Nunes dos Santos; Patricia Ramos Cury (Wolters Kluwer Medknow Publications, 2023)
Introduction: Saliva is involved in the transmission and spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); however, there are conflicting data regarding the detection rate of SARS-CoV-2 in the saliva. This study aims to investigate the presence of SARS-CoV-2 in the saliva of individuals with a mild form of coronavirus disease 2019 (COVID-19). Materials and methods: A sample of 110 participants who showed flu-like symptoms for 3 to 7 days and tested positive for SARS-CoV-2 after rapid antigen testing of nasopharyngeal swabs were included. Immediately after testing positive for COVID-19, the participants were asked to spit 1.5 mL saliva sample into sterile collectors. Salivary samples were homogenized and diluted, and viral nucleic acid was extracted and amplified by real-time reverse transcription polymerase chain reaction assays (qRT-PCR genes N1 and N2). A Ct value <40 was defined as a positive result. Results: The N1 and N2 genes were amplified in 98.2% of the participants. In one case (0.9%), only the N2 gene was amplified, and there was no amplification in another case. The virus load was high (Ct ≤ 25) in 9.3% of the participants, moderate (Ct between 25 and 30) in 31.5%, and low (Ct between 30 and 40) in 60.2%. Conclusion: SARS-CoV-2 was present in the saliva of most individuals with mild COVID-19, with majority having a low salivary concentration of the virus. Dental care should be postponed during the COVID-19 outbreak. For urgent treatment, infection prevention measures should be adopted.